POST-TRANSCRIPTIONAL SILENCING OF GA20OX1 IN POTATO - Malhotra, Kanam; Agarwal, Sandhya; Pattanayak, Debasis; Minhas, J S (Potato Journal, 2013)
Attempt had been made for post transcriptional silencing (PTGS) of gene encoding GA 20oxidase (GA20OX1) for development of dwarf potato genotypes which could have higher yield and harvest index under long days and high temperatures. Gene sequence was retrieved from Gene Bank and primers were designed for development of inverted repeat construct of GA20OX1 (IVGA). Partial cDNA fragments of GA20OX1 were amplified by one-step RT-PCR using total RNA of potato cultivar Kufri Giriraj. cDNA fragments were ligated into inverted repeat orientation to get IVGA gene construct. This gene construct along with sense and antisense gene constructs under the control of constitutive CaMV 35S promoter were used for potato transformation using binary plant transformation vector pBI121. Agrobacterium-mediated transformation of potato cultivar Kufri Giriraj was done and a total of 460 putative transgenic lines were developed. A sub-set of these lines are presently under glass house evaluation.